The socio-political situation and the spiritual environment impacting on the formation of the weltanschauung of the Nasiruddin Tusi - Nafisa , Qushshayeva (Indonesian Journal of Innovation Studies, 2019)
In this article, the socio-political environment and the mystic-philosophical worldview of Abu Ja'far Muhammad ibn Muhammad ibn Hasan Nasiruddin Tusi, who lived in the 13th century, recognized as the greatest philosopher in the history of philosophy and mysticism, left an indelible mark on the development of Islamic philosophy. The factors that have been shown are analyzed.